2022
DOI: 10.1177/08982643221091653
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality in 433 Nonagenarians Inside the Mugello Study: A 10 Years Follow-Up Study

Abstract: Objective to identify the predictors of mortality in a cohort of nonagenarians inside the “Mugello study” after 10 years follow-up. Methods Information on sociodemographic data, cognitive and functional status, lifestyle, medical history, and drug use was collected from 433 non-selected participants aged 90-99 years, living in the Mugello area (Italy). Participants were followed over 10 years and their dates of death were retrieved from the municipal registers. Cox regression analysis was used to determine sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…In community nonagenarians, relationships between functional independence and cognitive function, and extended lifespan have been recently found. In Pancani et al's (2022) study, impaired cognitive function and loss of functional independence were the stronger predictors of mortality. Some studies have suggested that dementia adversely influences clinical outcomes in patients hospitalized for acute diseases (Guijarro et al, 2010;Sampson, et al, 2009).…”
Section: Discussionmentioning
confidence: 74%
“…In community nonagenarians, relationships between functional independence and cognitive function, and extended lifespan have been recently found. In Pancani et al's (2022) study, impaired cognitive function and loss of functional independence were the stronger predictors of mortality. Some studies have suggested that dementia adversely influences clinical outcomes in patients hospitalized for acute diseases (Guijarro et al, 2010;Sampson, et al, 2009).…”
Section: Discussionmentioning
confidence: 74%